A Qualitative Analysis of Smoking Behavior from a Gender Perspective in Indonesia - Kodriati, Nurul; Rosemary, Rizanna (Universitas Airlangga, 2025)
Background: In Indonesia, smoking is very prevalent, mainly among men, causing a high prevalence of smoking-related diseases. In this country, smoking is linked to social construction rooted in how to become men and women. Male smoking is acceptable; otherwise, the social stigma associated with female smokers drives them to conceal their habits, making intervention difficult. Objective: The paper examined the gender aspect of smoking and communication in promoting health within a sensitive issue and context—smoking and gender in Indonesia. Method: This paper employed a thematic analysis of two doctoral theses on gender and smoking, each thesis representing either male or female aspects, to explore the relationship between gender values and smoking. Mutual factors contributing to men's and women's smoking behaviors were gender values related to smoking, the importance of different life stages, and children as an entry point for adult smoking cessation. Results: Tobacco control interventions may be hampered if these influences are undermined. Conclusion: It can be concluded, smoking-related health communication must consider gender variations and empower gender values.